THE PROCESSING OF THE RELATIVE CLAUSE IN SPANISH: INTERFERENCES OF THE DISTANCE FACTOR IN THE USE OF THE RESUMPTIVE PRONOUN - Camara, Aliana Lopes [UNESP] (Univ Nacional Colombia, Fac Ciencias Humanas, 2018)
The study inquires into the use of the resumptive pronoun in the restrictive relative clause, in order to verify the influence of the distance factor in the mobilization of this formal marker. From the theoretical perspective of emergentism, distance refers to the greater cost on working memory involved in resolving the filler-gap dependency, taking the distance between the nucleus and the lexical gap within the relative clause as a parameter. The article examines the hypothesis that the greater the distance between nucleus and gap, the greater the degree of difficulty in processing the relative clause. The data, which includes six varieties of Spanish and was selected from the Preseea project (Project for the Sociolinguistic Study of Spanish from Spain and America), was analyzed both quantitative and qualitatively. The analysis shows that distance triggers the use of the resumptive pronoun, which functions as a facilitator in the process of understanding, thus reducing the cost on working memory.
Keywords: emergentism; linguistic processing; relative clause; distance; relativization strategies; pronominal copy